Access to the Syn diastereomers of cryptophane cages using HFIP. Issue 20 (21st February 2022) - Della-Negra, Oriane; Cirillo, Yoann; Brotin, Thierry; Dutasta, Jean-Pierre; Saaidi, Pierre-Loic; Chatelet, Bastien; Martinez, Alexandre
Abstract : The use of the HFIP/bisulfate salt combination provides convenient and fast access to syn -cryptophanes. Abstract : Cryptophane cages can adopt either an anti or syn configuration that present different recognition properties. While the synthesis of anti -cryptophanes is well reported, the synthesis of syn -cryptophanes remains a challenge. Herein, we demonstrate that the use of HFIP as a co-solvent during the second ring closure reaction significantly affects the regioselectivity, providing easier access to the syn -cryptophane stereomers.